2018
DOI: 10.1111/jopr.12789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkaline Peroxides on the Surface of Cobalt Chrome Alloy: An In Vitro Study

Abstract: The various solutions tested did not have any deleterious effects on the Co-Cr alloy surface. Steradent, however, presented the smallest ionic release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
(106 reference statements)
0
12
0
10
Order By: Relevance
“…The metal disks were randomly distributed in 5 experimental groups (n = 11) according to the cleanser solutions used (Fig ). Initial surface topography analysis and qualitative evaluation of the surface composition of the Co‐Cr alloy was performed on one specimen of each group by scanning electron microscopy (SEM) and energy dispersive X‐ray spectroscopy (EDS) and measurement of the surface roughness values (n = 10). The specimens were then placed in plastic containers with 150 mL of cleanser solution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The metal disks were randomly distributed in 5 experimental groups (n = 11) according to the cleanser solutions used (Fig ). Initial surface topography analysis and qualitative evaluation of the surface composition of the Co‐Cr alloy was performed on one specimen of each group by scanning electron microscopy (SEM) and energy dispersive X‐ray spectroscopy (EDS) and measurement of the surface roughness values (n = 10). The specimens were then placed in plastic containers with 150 mL of cleanser solution.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical solutions have proven antimicrobial action and are effective in the removal of biofilm, having special importance in the remission of denture stomatitis . However, it has been reported that some cleansers promote adverse effects on the metallic surface, making them impracticable for use in RPD cleaning, since compatibility with the constituent materials of the denture is an important requirement for denture cleansers …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…No Brasil a ideia de que a perda dentária é um fenômeno natural que ocorre devido ao envelhecimento é aceito como fato cultural, porém é totalmente equivocada, pois isso se dá devido à falta de prevenção, informação e principalmente cuidados com a higiene oral que pode desencadear infecções locais ou sistêmicas (VASCONCELOS et al, 2019).…”
Section: Introductionunclassified